Altenberg–Teplice Caldera sourced Westphalian fall tuffs in the central and western Bohemian Carboniferous basins (eastern Variscan belt). Issue 4 (21st February 2022) - Tomek, Filip; Opluštil, Stanislav; Svojtka, Martin; Špillar, Václav; Rapprich, Vladislav; Míková, Jitka
ABSTRACT: Timing of magmatic activity of the late-Variscan Altenberg–Teplice Caldera was rather vaguely constrained. In this paper, we present five new laser ablation inductively coupled plasma mass spectrometry (LA–ICP–MS) U–Pb zircon ages, which along with published data indicate ~13 Myr lifetime. Formation of the Altenberg–Teplice Caldera commenced with the emplacement of the pre-caldera pluton at ~325–319 Ma, and terminated with the intrusion of the syn-collapse ring dykes and post-collapse granites at ~312 Ma. The main ignimbrite volcanism in the area of the ATC occurred at ~318–313 Ma and peaked at ~314–313 Ma. The latter corresponds to the age of the caldera-forming eruptions, which sourced the extra-caldera pyroclastic deposits. The same age yielded the rhyolite dyke swarm that fed the ignimbrite eruptions. Some pyroclastic fall deposits preserved in adjacent Carboniferous basins indicate similar ages of ~314–312 Ma including the widespread ~314 Ma Bělka tuff, which represents the main chronostratigraphic marker of this area. Its thickness and grain size progressively degrease from the ATC towards S and SW. This, together with the isopach map distribution and the available geochronological data suggest that the Bělka tuff was sourced from the Altenberg–Teplice Caldera. The Bělka tuff distribution and its association with the extra-caldera ignimbrites of the Altenberg–Teplice Caldera imply that this tuff is a co-ignimbrite fall deposit that accompanied pyroclastic density currents sourced from the caldera. The calculated minimum volume of fallout ash-tuffs and extra-caldera ignimbrite facies contribute 30 km 3 to the 350 km 3 (dense rock equivalent) estimates of the total Altenberg–Teplice Caldera products. Such volumes correspond well to similar modern analogues of collapse calderas of intermediate size.